Microstructural evolution of soft magnetic 49Fe-49Co-2V alloy induced by drilling. (April 2020) - Zhang, Yuan; Kang, Renke; Dong, Zhigang; Wang, Qing; Zhu, Xianglong; Xu, Rui; Guo, Dongming
Abstract: Mechanical drilling can change the microstructure of the regions near the hole wall, remarkably affecting the working performance of precision parts. The present work investigated the microstructural evolution in the regions from the drilled hole wall to the inner matrix of the soft magnetic 49Fe-49Co-2V alloy after the common drilling experiments were carried out. The microstructures and microhardness in different regions near the hole wall along the radial direction were characterized with OM, SEM, TEM, EBSD and Vickers Microhardness tester. The experimental results show that the nearest region to the hole wall is constituted of nano-sized refined grains. It exhibits a disordered BCC phase due to the rapid cooling from the high temperature during the drilling, different from the dual-phase of BCC and B2 of the matrix. The second-nearest region to the hole wall is distributed by a huge number of dislocations, leading to a maximum in microhardness. The microstructural evolution contributes to the variation of the microhardness, which increases firstly, reaches a maximum, and then decreases to the level of the matrix with the distance increasing from the hole wall. This variation tendency is discussed in light of both refined grain-boundary strengthening and dislocation strengthening mechanisms. Graphical abstract: Unlabelled Image Highlights: The influence of drilling on microstructure of 49Fe-49Co-2V has been investigated. A thin layer of refined grains occurs in the nearest region to the hole wall. A single BCC solid solution structure of 49Fe-49Co-2V can be attained by drilling. Dislocation density decreases with the distance to the hole wall increasing. Boundary and dislocation strengthening is the main mechanism for hardness increase.